PENDAMPINGAN STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN KEPADA PELAKU UMKM JAMU TRADISIONAL - Darulfadli, Iqbal; Fatimah, Dewi; Kuwartisen, Deri; Harpepen, Andi (CV. Kalimasada Group, 2025)
The goal of this community service project is to strengthen UMKM's capacity to use digital marketing tactics, particularly social media, to boost sales. In the past, the traditional herbal medicine UMKM